2015
DOI: 10.1113/jp270704
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ current facilitation determines short‐term facilitation at inhibitory synapses between cerebellar Purkinje cells

Abstract: Key pointsr Short-term facilitation takes place at GABAergic synapses between cerebellar Purkinje cells (PCs).r By directly patch clamp recording from a PC axon terminal, we studied the mechanism of short-term facilitation.r We show that the Ca 2+ currents elicited by high-frequency action potentials were augmented in a [Ca 2+ ] i -dependent manner.r The facilitation of synaptic transmission showed 4-5th power dependence on the Ca 2+ current facilitation, and was abolished when the Ca 2+ current amplitude wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 63 publications
(184 reference statements)
2
21
0
Order By: Relevance
“…They found that the onset of facilitation is rapid (τ on =2 ms) and following a return to resting calcium levels enhancement is short-lived (τ off =31 ms). The time course of paired-pulse facilitation of calcium current had a similar time course at the calyx of Held (Cuttle et al, 1998) and in Purkinje cell presynaptic boutons (Diaz-Rojas et al, 2015) (Figure 5C). These experiments were performed at room temperature, so it is likely that the onset and decay of facilitation of calcium entry is even more rapid at physiological temperatures.…”
Section: Use-dependent Increases In Calcium Entrymentioning
confidence: 81%
See 2 more Smart Citations
“…They found that the onset of facilitation is rapid (τ on =2 ms) and following a return to resting calcium levels enhancement is short-lived (τ off =31 ms). The time course of paired-pulse facilitation of calcium current had a similar time course at the calyx of Held (Cuttle et al, 1998) and in Purkinje cell presynaptic boutons (Diaz-Rojas et al, 2015) (Figure 5C). These experiments were performed at room temperature, so it is likely that the onset and decay of facilitation of calcium entry is even more rapid at physiological temperatures.…”
Section: Use-dependent Increases In Calcium Entrymentioning
confidence: 81%
“…High-frequency (40 Hz) stimulation does not lead to spike broadening in presynaptic boutons of cerebellar interneurons (Pouzat and Hestrin, 1997; Rowan et al, 2014). Synapses made between cultured Purkinje cells facilitate, but waveform changes are not responsible for facilitation (Diaz-Rojas et al, 2015). …”
Section: Use-dependent Increases In Calcium Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…A ; Díaz‐Rojas et al . ; Kawaguchi & Sakaba, ). Cultured PCs were labelled with EGFP by an AAV vector serotype 2, which shows a relatively specific transfection of PCs, and the fluorescence was used to precisely position a patch pipette with a small tip at the selected axonal varicosity.…”
Section: Resultsmentioning
confidence: 97%
“…Electrophysiological experiments on cultured PCs were performed similarly to previous studies (Díaz‐Rojas et al . ). Whole‐cell patch clamp recording from a cultured PC was performed with an amplifier (EPC10, HEKA, Germany) in a Hepes‐buffered extracellular solution containing (in m m ): 145 NaCl, 5 KCl, 2 CaCl 2 , 1 MgCl 2 , 10 Hepes, and 10 glucose (pH 7.3, 300 mOsm (kg H 2 O) −1 ).…”
Section: Methodsmentioning
confidence: 97%